Preferensi Civitas Akademika sebagai Dual Banking Customer dalam Memilih Jasa Perbankan Syariah - Muniroh, Masbakhatul; Sula, Atik Emilia (Journal of Sharia Economics, Banking and Accounting, 2025)
This research is motivated by the phenomenon of brand switching among banking customers, the interest of non-Muslims in several areas that use Islamic banks, and the existence of Muslim communities that prefer conventional banks. This study aims to identify and determine the dominant aspects in choosing banking services based on the preferences of active customers of Islamic banks and conventional banks (dual banking customers). The research method used is descriptive qualitative with a case study approach. Informants were selected based on certain criteria, including being active customers of Islamic banks and conventional banks and being academics at a university. The results of the study show that active customers of Islamic banks and conventional banks (dual banking customers) decided to choose conventional bank services because of aspects of service quality, external banks, bank locations, and network and technology availability, then the decision to choose Islamic bank services was caused by aspects of perceived reputation, customer rationality, and external banks.